Sprememba političnega vedenja v obdobju volilne kampanje - Novak, Meta (Družboslovne razprave, 2014)
An election campaign is a special sort of information campaign. Election candidates have an opportunity during this time to inform voters about themselves, their positions and programmes. At the same time, voters have an opportunity to acquire information needed to make an informed decision. We were interested to ascertain if during an election campaign any changes in political behaviour can be noticed. We observed a very narrow segment of political behaviour, namely political activation. We used data from the Politbarometer survey from 1996 until 2013 and noticed that during an election campaign the share of non-response to "for whom would you vote" question and an orientational "left-right" question was lower. That is true for both presidential and parliamentary elections.
Keywords: election; Elections; Volitve; Volilne kampanje; Election campaigns; Political behavior; Politično vedenje; Slovenia; Slovenija; volilci; javno mnenje